On pedagogy of a Soil Science Centre for Doctoral Training - Haygarth, Philip M.; Lawrenson, Olivia; Mezeli, Malika; Sayer, Emma J.; McCloskey, Christopher S.; Evans, Daniel L.; Kirk, Guy J. D.; Tye, Andrew M.; Chadwick, David R.; McGrath, Steve P.; Mooney, Sacha J.; Paterson, Eric; et al. (Wiley, 2021)
Here we describe and evaluate the success of a multi-institutional Centre for Doctoral Training (CDT), which was established to address a UK skills shortage in Soil Science. The government-funded ‘STARS’ (Soils Training And Research Studentships) CDT was established in 2015 across a range of universities and research institutes in the UK. It recruited 41 PhD students equitably split across the institutions under four core research themes identified as being central to the national need, namely, (1) Understanding the soil–root interface, (2) Soils and the delivery of ecosystem services, (3) Resilience and response of functions in soil systems and (4) Modelling the soil ecosystem at different spatial and temporal scales. In addition, the STARS CDT provided a diverse skills programme, including: Holistic training in soils, the promotion of collegiality and joint working, strategies to promote science and generate impact, internships with end users (e.g., policymakers, industry), personal wellbeing, and ways to generate a lasting soils training legacy. Overall, both supervisors and students have reported a positive experience of the CDT in comparison to the conventional doctoral training programmes, which have less discipline focus and little chance for students to scientifically interact with their cohorts or to undertake joint training activities. The STARS CDT also allowed students to freely access research infrastructure across the partner institutions (e.g., long-term field trials, specialised analytical facilities, high-performance computing), breaking down traditional institutional barriers and thus maximising the students' potential to undertake high-quality research. The success and legacy of the STARS CDT can be evidenced in many ways; however, it is exemplified by the large number and diversity of journal papers produced, the lasting collaborations, final career destinations, and creation of a web-based legacy portal including new and reflective video material.
Keywords: pedagogy; postgraduate learning; soil science; doctoral training; upskilling